Profile of patients with HPV infection at the regional hospital of Saint-Louis, Senegal - Thiam, Ousmane; S. O. W., Djibril Bahaid; L. O., Seynabou; S. A. R. R., Cherif Cheikh Tourade (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Objectives of current study was to define the sociodemographic characteristics of patients, to determine the frequency of HPV infection at the CHRSL and to describe factors associated with HPV infection. Methods: This was a prospective cross-sectional study conducted in the gynecology-obstetrics department of the Saint Louis Regional Hospital Center from November 11, 2019 to November 11, 2021, a period of 24 months. We studied sociodemographic, clinical and test results characteristics. Samples were taken from patients in the gynaecological position using a dedicated kit (cytobrush and tube). Viral research was carried out using the Atila Biosystems device for amplification and detection of viral DNA. This test genotypes HPV 16, 18 and 45, and detects 12 other HR HPVs (31, 33, 35, 39, 51, 52, 56, 58, 59, 66 and 68) simultaneously using three probes labelled with different fluorophores. Analysis was performed using Epi-Info software and Excel 2010. Results: The study population comprised 128 patients. The mean age of the patients was 41.95 years, with extremes of 23 and 70 years. They were married (92.97%) and housewives (46.88%). Almost all patients (77.34%) were genitally active. The average age at marriage was 21.78 years, and polygamous households predominated (53.91%). The average age at first intercourse was 20.05 years. The average age at first pregnancy was 21.78. Over (57.81%) of patients had at least two partners. Incense was used in 97.66% of cases. The viral HPV test was positive in (38.28%) of patients. High-risk papillomaviruses were the most common, at 63.27%. Colposcopy was performed in 17.19%; normal and satisfactory in (63.64%) of patients, with 22.27% of cervical biopsies, and histology showed one CIN2 and two CIN3. Therapeutically, one thermoablation and two hysterectomies were performed. Conclusions: HPV viral typing in primary screening for cervical cancer offers opportunities and remains realistic and feasible in less developed countries such as Senegal, despite modest resources.